Development of the self-directed RECEIVE Forgiveness workbook: a Christian-sensitive resource to support experiencing reconciliation with God - Cowden, Richard G.; Rutledge, Jonathan C.; Jackson-Meyer, Katherine; Cook, Kaye V. (Frontiers in Psychology, 2025)
Divine forgiveness is a central concept in many theistic religions, including Christianity, which has a rich and longstanding history of doctrine, spiritual practices, and rituals addressing or reinforcing the idea that God forgives. Providing empirical support for the role that forgiveness from God plays in the lives of Christians, a growing body of literature suggests that divine forgiveness may have important implications for human flourishing. Practical resources that are biblically aligned and developed through interdisciplinary collaboration among humanists (e.g., theologians) and social scientists (e.g., psychologists) could complement traditional religious customs and equip healthcare professionals with spiritually integrated tools for serving self-identifying Christian clients. To this end, we developed the RECEIVE Forgiveness workbook as a brief, self-directed workbook intervention to support Christians in experiencing reconciliation with God after becoming aware of personal sin. This brief report describes the first phase of the workbook development process, including its theoretical foundations, central change objective, and engagement targets. After summarizing feedback from Christian religious leaders, healthcare professionals who serve self-identifying Christian clients/patients, and lay Christians, we describe how this input was incorporated into refinements aimed at strengthening the practical utility of the workbook. While rigorous empirical evaluation is needed to examine the efficacy of the RECEIVE Forgiveness workbook, we discuss the potential for this Christian-sensitive intervention to promote spiritual well-being and support flourishing among the Christian population.